1975
DOI: 10.1136/bmj.2.5973.719
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heredity and environment in determination of skinfold thickness in children.

Abstract: SummaryTriceps and subscapular skinfold thicknesses were measured in 222 pairs of like-sex twins (78 monozygotic and 144 dizygotic) aged 3-15 years. Log transformations of the measurements were standardized for age and sex and the results used to estimate heritability-that is, the proportion of total variation determined by genetic factors. The overall contribution of non-genetic familial effects was small. There were appreciable differences in heritability between limb and trunk fat and between the sexes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

1985
1985
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(44 citation statements)
references
References 7 publications
2
40
0
2
Order By: Relevance
“…The Hereditary Abilities Study initiated in 1952 was a comprehensive study performed in the United States to investigate heritability of physical traits, including measures of adiposity (birth weight, body weight, and waist circumference) among monozygous and dizygous twins, which demonstrated that the greater part of variance for these traits was genetically determined (Clark 1956). These findings were consistent with other studies reported over 20 years later indicating a high heritability of body weight among monozygous and dizygous twins (Brook et al 1975;Borjeson 1976;Feinleib et al 1977). However, it became apparent that genetic susceptibility interacts with undefined environmental factors to increase adiposity and body weight, in what has formally become known as a ''gene-environment interaction'' and defined as Fig.…”
Section: Heritability Of Body Weight and Interaction With Environmentsupporting
confidence: 91%
“…The Hereditary Abilities Study initiated in 1952 was a comprehensive study performed in the United States to investigate heritability of physical traits, including measures of adiposity (birth weight, body weight, and waist circumference) among monozygous and dizygous twins, which demonstrated that the greater part of variance for these traits was genetically determined (Clark 1956). These findings were consistent with other studies reported over 20 years later indicating a high heritability of body weight among monozygous and dizygous twins (Brook et al 1975;Borjeson 1976;Feinleib et al 1977). However, it became apparent that genetic susceptibility interacts with undefined environmental factors to increase adiposity and body weight, in what has formally become known as a ''gene-environment interaction'' and defined as Fig.…”
Section: Heritability Of Body Weight and Interaction With Environmentsupporting
confidence: 91%
“…In addition, we found three twin studies that had pooled information on children at different ages. [27][28][29] We did not limit our search to weight, but except one early twin study, 27 all of these studies had used BMI or relative weight as an indicator of obesity. Two twin studies represented Korean population, 16,19 one Taiwanese population 29 and one had pooled information from four East Asian populations, 30 but otherwise the studies were conducted in the Caucasian populations.…”
Section: Search Strategymentioning
confidence: 99%
“…Also, studies of the heritability of skinfold thicknesses in children yield similar results. 13,18,19 Adoption studies, on the other hand, show only moderate effects of genes (30 ± 40%) on variation of BMI and skinfolds, and family studies generally yield estimates of heritability intermediate between the twin and adoption studies. 20 Results from longitudinal studies support the suggestions from cross-sectional data that there are effects of genes on BMI that are age-speci®c.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found greater heritability of body weight in males than in females, 8,10 others the opposite. 5,7,16,19 Twin cohorts of different sizes from different ethnic backgrounds are frequently studied, but it is not known, whether the results can be generalized to the singleton population. Growth characteristics of twins have been compared to those of singletons 21 ± 25 but, again, never in nationwide samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation